The Influence of Leadership Style, Discipline, and Communication of The Head of The Room on Nurse Performance: In the 3rd Class Inpatient Room of Putri Hijau Hospital TK II Medan in 2022 - Ivone Rifasha; Sofiyan Sofiyan; Elly Romy; Abednego Suranta Karo (Jurnal of Management and Social Sciences, 2024)
Leadership in nursing is the application of influence and guidance aimed at all nursing staff to create trust and obedience so that there is a willingness to carry out tasks in order to achieve common goals effectively and efficiently. This study aims to determine whether the influence of the influence of leadership style, discipline, and communication of the head of the room on the performance of nurses (in the 3rd class inpatient room of Putri Hijau Tk Ii Medan Hospital in 2022). The sampling method in this study was simple random sampling, the population in this study were all nurses of class 3 inpatient rooms at RSPH Medan in 2022 as many as 130 people. The sample used was 98 respondents. The data collection technique used is primary data in the form of questionnaires and secondary data obtained through documentation studies. The data analysis technique uses quantitative data processed with the SPSS version 29 program, the results in this study are t test and f test. The results obtained in this study show, 1) there is a significant effect of Leadership Style (X1) on nurse performance (Y), 2) there is a significant effect of Discipline (X2) on nurse performance (Y), 3) there is a significant effect of Communication (X3) on nurse performance (Y), 4) there is a simultaneous significant effect of Leadership Style (X1), Discipline (X2), and Communication (X3) on nurse performance (Y).